Vascular plant biodiversity of Katannilik Territorial Park, Kimmirut and vicinity on Baffin Island, Nunavut, Canada: an annotated checklist of an Arctic flora - Saarela, Jeffery M.; Sokoloff, Paul C.; Gillespie, Lynn J.; Bull, Roger D. (Frontiers in Ecology and Evolution, 2023)
The Arctic ecozone is undergoing a rapid transformation in response to climate change. Establishing a baseline of current Arctic biodiversity is necessary to be able to track changes in species diversity and distribution over time. Here, we report a vascular plant floristic study of Katannilik Territorial Park, Kimmirut and vicinity within Circumpolar Arctic Bioclimate Subzone D on southern Baffin Island, Nunavut, Canada. We compiled a dataset of 1596 collections gathered in the study area throughout the last century, including 838 we made in 2012. The vascular flora comprises 35 families, 98 genera, 211 species, two nothospecies and seven infraspecific taxa. We newly recorded 51 taxa in 22 families in the study area: Erigeron eriocephalus, Taraxacum holmenianum (Asteraceae), Draba arctica, D. fladnizensis, D. lactea (Brassicaceae), Campanula rotundifolia (Campanulaceae), Arenaria longipedunculata, Honckenya peploides subsp. diffusa, Sabulina rossii, Silene uralensis subsp. uralensis, Viscaria alpina (Caryophyllaceae), Carex brunnescens subsp. brunnescens, C. krausei, C. microglochin, C. subspathacea, C. williamsii, Eriophorum scheuchzeri subsp. arcticum (Cyperaceae), Andromeda polifolia, Orthilia secunda subsp. obtusata (Ericaceae), Oxytropis podocarpa (Fabaceae), Luzula groenlandica (Juncaceae), Triglochin palustris (Juncaginaceae), Utricularia ochroleuca (Lentibulariaceae), Huperzia continentalis (Lycopodiaceae), Montia fontana (Montiaceae), Corallorhiza trifida, Platanthera obtusata subsp. obtusata (Orchidaceae), Hippuris lanceolata, H. vulgaris, Plantago maritima (Plantaginaceae), Calamagrostis neglecta subsp. groenlandica, C. purpurascens, Festuca prolifera var. lasiolepis, F. rubra subsp. rubra, F. rubra subsp. arctica, Hordeum jubatum subsp. jubatum, Leymus mollis subsp. mollis, L. mollis subsp. villosissimus, Puccinellia vaginata (Poaceae), Primula egaliksensis (Primulaceae), Cryptogramma stelleri (Pteridaceae), Coptidium × spitsbergense (Ranunculaceae), Potentilla crantzii, P. hyparctica subsp. ...